EFFECTIVENESS OF GROUP WORK IN TEACHING A FOREIGN LANGUAGE - Niyatova, Maftuna (Журнал иностранных языков и лингвистики, 2023)
The article presents a brief background about group work and its nature, the importance in teaching a foreign language and the utilizing of it in schools, colleges or higher education. This paper provides detailed suggestions with illustrations, background of previous researches, foundations, results of them and so on. The authors and researchers with all level may use in practical and theoretical researches with the help of data in the article.